2010
DOI: 10.1093/hmg/ddq212
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression of polyglutamine-expanded huntingtin by mouse striatal astrocytes impairs glutamate transport: a correlation with Huntington's disease subjects

Abstract: Huntington's disease (HD) is a neurodegenerative disorder previously thought to be of primary neuronal origin, despite ubiquitous expression of mutant huntingtin (mHtt). We tested the hypothesis that mHtt expressed in astrocytes may contribute to the pathogenesis of HD. To better understand the contribution of astrocytes in HD in vivo, we developed a novel mouse model using lentiviral vectors that results in selective expression of mHtt into striatal astrocytes. Astrocytes expressing mHtt developed a progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
271
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(284 citation statements)
references
References 50 publications
7
271
1
Order By: Relevance
“…From a different perspective, expression and function of the glutamate transporter GLT-1 can be modulated up or down during astrogliosis depending on the nature of the insult and time after the insult, and this regulation can impact outcome by influencing extracellular glutamate levels and the potential for neuronal excitotoxicity (Bianchi et al 2013). The mTORAkt-NF-kB pathway is one molecular signaling mechanism that can modulate astrocyte expression of Glt-1 (Pawlak et al 2005;Faideau et al 2010;Ji et al 2013). Findings such as these support a model in which many different specific signaling mechanisms can trigger different specific molecular, morphological, and functional changes in reactive astrocytes.…”
Section: Selective Regulation Of Specific Functions and Effects Of Asmentioning
confidence: 99%
“…From a different perspective, expression and function of the glutamate transporter GLT-1 can be modulated up or down during astrogliosis depending on the nature of the insult and time after the insult, and this regulation can impact outcome by influencing extracellular glutamate levels and the potential for neuronal excitotoxicity (Bianchi et al 2013). The mTORAkt-NF-kB pathway is one molecular signaling mechanism that can modulate astrocyte expression of Glt-1 (Pawlak et al 2005;Faideau et al 2010;Ji et al 2013). Findings such as these support a model in which many different specific signaling mechanisms can trigger different specific molecular, morphological, and functional changes in reactive astrocytes.…”
Section: Selective Regulation Of Specific Functions and Effects Of Asmentioning
confidence: 99%
“…On the membranes of astrocytes, which are the major subtype of glial cells, there are two types of glutamate transporters (GLT-1 and GLAST) that do most of the work in clearing extracellular excitatory neurotransmitters [7,8] . It has been shown that small fragments of N-terminal mutant Htt (such as N-208, N-171), which were reported to be more pathogenic than full-length mutant Htt, caused decreased expression of GLT-1 [2,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Energy is required for astrocytes to accomplish GLU transport (Azarias et al, 2011), and a corresponding decline in the astrocytic expression of GLU transporters seems to reach a point where the striatum can no longer keep up with the behavior-related surges of GLU necessary to generate striatal bursting activity (Wilson, 2004). It seems this occurs despite observations that astrocytes initially proliferate in HD, perhaps as a compensatory strategy (Faideau et al, 2010). It is also relevant to pre-HD that developmental changes seem to take place between youth and later adulthood regarding astrocytic participation in GLU clearance.…”
Section: Presymptomatic Neurotransmitter Releasementioning
confidence: 96%